Audubon butterfly DVD : essentials for beginners and gardeners [videorecording (DVD)] - Opler, Paul A.; Ebner, Jim (MasterVision, 2008)
Presents instruction on identifying butterflies found across the United States. Covers butterfly biology, lifecycles, and behavior. Explains how to attract butterflies to backyard gardens.